Gender role variations after a human-induced flood : a case study of hydropower dam collapse in Attapue Province, Lao PDR - Phonenipha Philangam; Kusakabe, Kyoko; Doneys, Phillippe; Thi Phuoc Lai Nguyen; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
Resource rich Laos is a land locked developing country that highly rely on the exploitation its natural resources namely wood based industry, mining and hydropower dam construction. These types of development are not sustainable except hydropower dam that could imply in the improvement of the livelihood of rural household through irrigated agricultural production and fisheries. The Dam construction, however pose some risk starting from its construction and Laos has experience several Dam collapses at different scale. The most affected is the incident in Attapeu province in Southern Laos that turned to be a major disaster. Such incidents have a great impact to the local people. As a result, it is critical to look at the effects of disasters on men and women's lives, as well as the challenges they face as a consequence of disaster. Data information has collected in Khokkong Village, Sanamxay District in Attapue Province through key informant interviews, questionair survey and in-depth interviews have been conducted for this study. The research explores the pattern of the gender livelihood pre and post disaster to find out the change in the occupation of men and women in different categories of household impacted by the flood disaster and the challenges that they face. Findings suggest that women and men occupation had changed the pattern into a more collaborative management of their day to day lives and a more organized paid and unpaid work as the result ofliving condition change. For this it is found that women are more vulnerable in every aspect of activities. The result ofthis research could be used to correctly understand the problem that occurs at household level and use the findings as supporting justification to address needy assistance to respond to the impact and provide correct remedy.
A thesis submitted in patial fulfillment of the requirements for the degree of Master of Science in Gender and Development Studies
Thesis (M. Sc.) - Asian Institute of Technology, 2021
Keywords: Induced seismicity -- Lao; Disaster relief -- Developing countries; Women -- Relations -- Lao